Investigation of Heat Transfer Influences on Performance of Air-Standard Irreversible Dual-Miller Cycle - Gonca, Guven; Sahin, Bahri; Ust, Yasin (AMER INST AERONAUTICS ASTRONAUTICS, 2015)
An analysis has been performed for an irreversible dual-Miller cycle with late inlet valve closing (LIVC), taking into consideration the influences of heat transfer loss and internal irreversibility for adiabatic compression and expansion processes. In the analyses, the influences of the Miller cycle ratio, pressure ratio, inlet temperature, heat transfer, and combustion constants have been examined. The maximum values of nondimensional power output and thermal efficiency with respect to engine design parameters, as well as optimal cutoff ratios and pressure ratios at maximum nondimensional power output and maximum thermal efficiency with respect to heat transfer and combustion constants, have been computationally obtained.
Keywords: VARIABLE SPECIFIC-HEATS; DIESEL-ENGINE; THERMODYNAMIC SYSTEMS; WORKING FLUID; OPTIMAL PATHS; EFFICIENCY; EMISSION; FRICTION; Thermodynamics; Engineering